Effect of straw and rainfall on Amaranthus hybridus control with Imazethapyr + Flumioxazin - Victor Volante Garcia; Marcelo Augusto de Aguiar e Silva; Giliardi Dalazen (Semina: Ciências Agrárias, 2024)
The use of herbicides applied at pre-emergence is an important measure for managing Amaranthus hybridus. However, the presence of straw and rainfall regime after application may alter the efficacy of these herbicides. This study was carried out with the objective of evaluating the effect of different straw mass on the soil surface and different rainfall regimes on the efficacy of imazethapyr + flumioxazin in controlling Amaranthus hybridus. Three greenhouse experiments were conducted and replicated for two years. Experiment 1 consisted of five Brachiaria humidicola straw mass (0, 2, 4, 6 and 8 Mg ha-1) with 20 mm rainfall simulation after herbicide application; in experiment 2, six times to the first rainfall (0, 3, 6, 9, 12 and 15 days) after herbicide application were assessed; and experiment 3 involved four rainfall volumes (0, 10, 30 and 50 mm) after herbicide application. The presence of straw did not alter the efficacy of imazethapyr + flumioxazin, even at the highest mass assessed (8 Mg ha-1) and rainfall of 20 mm. In the absence of herbicide, the highest B. humidicola weight reduced emergence of A. hybridus by 63% when compared to the straw-free treatment. The herbicide imazethapyr + flumioxazin demonstrated flexibility in response to rainfall regime, with total control of A. hybridus even after15 days of drought and up to 50 mm of rain after spraying. The herbicide imazethapyr + flumioxazin was effective against A. hybridus in all straw and rainfall situations evaluated.